Sleep hygiene a neglected paediatric identity – A cross-sectional study - Pradeep Maniraj; Podhini Jegadeesan; Shanthi Ananthakrishnan (Journal of Family Medicine and Primary Care)
Background: Sleep is the physiological need of any human being; its role in paediatric mental and physical development is irreplaceable. However, in recent days, the rising trend of childhood obesity makes it essential to assess the sleep hygiene of the children to know if there is any adjacent association. Objectives: 1. To estimate the prevalence of poor sleep quality using Sleep Hygiene Index Scoring. 2. To determine the association of sleep quality with academic performance and body mass index among the school children. Materials and Methods: The present cross-sectional study was conducted among 322 children aged between 7 and 12 years attending paediatric OPD of a private tertiary care hospital, Puducherry. Using Sleep Hygeine Index scoring with the cut off 16, prevalence of poor sleep quality was assessed and its association with BMI and academic performance was determined. Frequency, proportion, and Chi-square test were used for analysis; P value < 0.05 was considered statistically significant. Results: The mean age of the participants was 8.8 ± 2 years, and most of them were boys. Around 53% of the children had poor quality of sleep, and there was a positive association between poor sleep quality with obesity (P value: 0.0003) and unfavourable academic performance (P value: 0.00001). Conclusion: Sleep hygiene importance should be taught to the parents and periodical assessment helps in predicting the neglected reason for obesity and poor academic performance, which could be managed easily with small lifestyle changes.